Benefits of prescribing telemonitored exercises in patients with ankylosing spondylitis in the covid-19 pandemic: case series - Facci , Ligia Maria; da Silva, Daniela Wosiack; dos Passos , Ana Eliza; Mazziero , Antonio Carlos; Rodrigues, Vinicius Moreto Guisso (Seven Editora, 2023)
Introduction: Ankylosing spondylitis (AS) is a complex disease characterized by inflammation of the spine and large joints. Considering the various losses caused by the COVID-19 pandemic, especially in individuals with chronic diseases due to cancellations of appointments and treatments, telemonitoring or telecare has become a good alternative for patients with AS, providing continuity of care. Objectives: To evaluate the effects of telemonitored exercises in patients with AS during the COVID-19 pandemic. Methods: Seven patients diagnosed with AS were included, evaluated, and followed up via messaging application. In the evaluations, several clinical issues were investigated, such as pain (VAS), stiffness, sleep, functionality (BASFI), quality of life (HAQ-S), and exercise frequency. The prescription and telemonitoring of home exercises occurred for 10 months by sending evaluation forms, videos with exercise guidelines, and monitoring via messaging application. Results: The frequency of exercises performed by the patients was a median between 165 and 217 minutes per week. No patient reported any adverse effect to the exercises, and it was possible to observe the improvement of pain and morning stiffness when comparing the variables of the initial and final evaluations, but without statistically significant differences. A strong correlation was found between functionality, morning pain, and momentary pain, as well as between momentary pain and stiffness time. Conclusion: Patients with AS had adherence to telemonitored exercises, as well as important benefits regarding functionality, sleep quality, morning pain intensity, quality of life, pain, and stiffness. In the patients with AS studied it was observed that the lower the pain intensity and the time of morning stiffness, the better the functionality. DOI:https://doi.org/10.56238/emerrelcovid19-011